Traditional Plant-Based Forms of Treatment of Fungal Infections in Suriname Phytochemical and Pharmacological Rationale - Mans, Dennis R.A (IntechOpen, 2022)
Plant-based traditional medicines are abundantly used in the Republic of Suriname (South America) for treating a wide variety of conditions including fungal infections. This book reviews nine plants with antifungal potential and explains the phytochemical and pharmacological support for their apparent usefulness against fungal infections. These data are placed within the context of some health aspects and the healthcare structure of Suriname, following observations about the characteristics and taxonomy of fungi and their significance to humans and information about fungal infections and their allopathic forms of treatment. The book concludes with a section about the significance of these Surinamese herbal antifungal substances to mainstream antifungal treatments.